Cytoadherence and ultrastructure of Plasmodium falciparum-infected erythrocytes from a splenectomized patient. - Ho, M (1992)
In malarial infections of primates, the spleen has been shown to modulate parasite antigen expression on the surfaces of infected erythrocytes. The processes affected include cytoadherence, which is central to the pathophysiology of severe falciparum malaria, and the related phenomenon of rosette formation. In this study, the cytoadherence and rosette formation behaviors of Plasmodium falciparum-infected erythrocytes from a splenectomized patient were examined during the first erythrocytic cycle in vitro. Ultrastructural studies were also performed. Infected erythrocytes were found to cytoadhere to C32 melanoma cells via leukocyte differentiation antigen CD36 but not intercellular adhesion molecule 1. They also displayed on their surfaces electron-dense knobs similar in structure and density to those on infected erythrocytes from intact hosts. These findings may reflect a stable cytoadherent phenotype of the parasite isolate that is unaffected by the absence of the spleen. Alternatively, the modulating role of the spleen may have been assumed by other organs of the mononuclear phagocytic system in a previously infected individual. No rosette formation was observed, but as not all natural isolates form rosettes, this observation may or may not be related to the asplenic status of the patient. Parasite and host factors appear to be important in determining the effect of splenectomy on cytoadherence and rosette formation in human falciparum malaria.